Management options, technologies and strategies for minimised mycotoxin contamination of rice - Gummert, M.; Balingbing, C.; Barry, G.; Estevez, L. (Brill, 2009)
Ninety percent of the world's rice is produced and consumed in Asia. Millions of rice producers are resource-poor farmers with a rice area of less than one hectare. Yield increase and the introduction of double-cropping systems have ensured that rice production has kept up with an increasing demand. However, the increased quantities of grain and the second harvest, which is often in the wet season, have increased the problems in traditional postharvest systems. This can be particularly severe in the humid tropics, where post-harvest losses occur because of outdated management practices and technologies, and delays in post-harvest operations. Fungal infestation of rice grains can lead to discoloration, which results in price reductions in most markets. This can also result in rice being contaminated with mycotoxins, which is less visible to consumers. Contamination with ochratoxins, aflatoxins, and other mycotoxins have occasionally been reported in the literature. In the past, this was not seen as a significant problem and the focus was on other commodities such as maize and peanuts. However, recent studies and a massive recall of food products in Japan in September 2008, including sake, shoshu, and rice crackers made from imported rice from China and Vietnam, which were tested positive for aflatoxins, and also for pesticide residues, have renewed interest in looking at mycotoxin problems in rice. Exploratory studies in the Philippines compared best practice post-harvest management with the traditional management practices often used by smallholder farmers and small processors. It was concluded that synthesis of aflatoxin B1 is very likely in suboptimal post-harvest systems, with levels far above legislative limits. This indicates that there might be a considerable mycotoxin problem in rice from smallholder post-harvest operations. Improved post-harvest management options and technologies are available for diversified small-scale post-harvest systems. Small-scale combine harvesters, affordable and simple mechanical dryers and hermetic storage systems can help to avoid delays in the post-harvest chain and thus reduce mycotoxin contamination of rice. The development of strategies to scale out these improved practices and technologies to a large number of smallholder farmers will continue to be the main challenge.